Pengaruh Struktur Organisasi terhadap Kinerja Pegawai pada PT Medco E dan P Indonesia Sumatera Selatan - Heriyanto Heriyanto; Laila Nurfitrah Lubis; Debbie Yuari Siallagan (Eksos, 2020)
With the existing organizational structure and being entrusted with a number of employees to carry out company activities, it brings hope for a change in work patterns for the better which can be proven by good performance. The completion of organizational goal that is determined by human factors and existing systems. From the description on the background of the problem above, the writer will analyze weather there is any influence on the organizational structure of PT Medco E and P Indonesia on employee performance. The research method used was an explanatory survey (explanatory). To reveal the influence of independent variables and dependent variables using quantitative methods and this research hypothesis is analyzed statistically, where the independent variable (independent) is analogized into X namely Organizational Structure and the dependent variable (dependent) is analogized into Y namely Employee Performance. The result of the data analysis is the score of Fcount 25.459 and the score of Ftable 3.97 with a significance score 0.000. This means that the score of Fcount> Ftable and sig <0.05 so it can be concluded that H1 is accepted. It means that there is an influence between the variables of Organizational Structure on Employee Performance and the conclution of this research is the application of job specialization, Departmentalization, Chain of Command, Span of Control, Centralization / Decentralization and Formalization, in the organizational structure has implications for improving employee performance at PT Medco E and P Indonesia South Sumatra.